Robotic Applications in Cranial Neurosurgery: Current and Future. Issue 6 (30th June 2021) - Ball, Tyler; González-Martínez, Jorge; Zemmar, Ajmal; Sweid, Ahmad; Chandra, Sarat; VanSickle, David; Neimat, Joseph S; Jabbour, Pascal; Wu, Chengyuan
Abstract: Robotics applied to cranial surgery is a fast-moving and fascinating field, which is transforming the practice of neurosurgery. With exponential increases in computing power, improvements in connectivity, artificial intelligence, and enhanced precision of accessing target structures, robots are likely to be incorporated into more areas of neurosurgery in the future—making procedures safer and more efficient. Overall, improved efficiency can offset upfront costs and potentially prove cost-effective. In this narrative review, we aim to translate a broad clinical experience into practical information for the incorporation of robotics into neurosurgical practice. We begin with procedures where robotics take the role of a stereotactic frame and guide instruments along a linear trajectory. Next, we discuss robotics in endoscopic surgery, where the robot functions similar to a surgical assistant by holding the endoscope and providing retraction, supplemental lighting, and correlation of the surgical field with navigation. Then, we look at early experience with endovascular robots, where robots carry out tasks of the primary surgeon while the surgeon directs these movements remotely. We briefly discuss a novel microsurgical robot that can perform many of the critical operative steps (with potential for fine motor augmentation) remotely. Finally, we highlight 2 innovative technologies that allow instruments to take nonlinear, predetermined paths to an intracranial destination and allow magnetic control of instruments for real-time adjustment of trajectories. We believe that robots will play an increasingly important role in the future of neurosurgery and aim to cover some of the aspects that this field holds for neurosurgical innovation.